1971
DOI: 10.1172/jci106630
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the esophageal wall

Abstract: A B S T R A C T Pressure-diameter curves of the esophagus were obtained to define its mechanical properties. The mucosal contribution to the strength of the esophagus was negligible until the outer diameter almost doubled, suggesting that small intraluminal pressures are held by the muscle layer alone. For larger deformations mucosal contribution increased and at failure the mucosa held over one-half of the failure pressure of the esophagus.The paths followed during loading and unloading are different and exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Pressure-diameter curves were also obtained for the esophagus and the LES in the isolated but in situ preparation of the esophagus described previously (13). In this preparation, the rats were anesthetized and the esophagus was exposed after removing the heart, lungs, and other mediastinal structures.…”
Section: Methodsmentioning
confidence: 99%
“…Pressure-diameter curves were also obtained for the esophagus and the LES in the isolated but in situ preparation of the esophagus described previously (13). In this preparation, the rats were anesthetized and the esophagus was exposed after removing the heart, lungs, and other mediastinal structures.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental study of the rat [12] also demonstrated that the mucosal contribution to the strength of the esophagus was negligible until the outer diameter of the esophagus was almost doubled. When the esophagus was dilated to near its failure diameter (3 times the resting diameter), the mucosa was responsible for more of the tensile strength of the esophagus than the muscular layer.…”
Section: Discussionmentioning
confidence: 96%
“…There has been one report in animals relating the size of the esophagus at resting pressures to the size of the esophagus at its point of napture [12]. The esophagus of the rat increased from a resting diameter of 1.7 mm to an average of 5 mm before rupture occurred.…”
Section: Discussionmentioning
confidence: 99%
“…After the creep step, the sample was deflated. In total, 16 inflation tests were performed on each experimental sample according to different inflated top pressures, such as 4, 6,8,10,14,18,22,26,30,34,38,46, 54, 62, 70 and 78 mmHg. The pressure range of experimentations, such as 4-78 mmHg, and the pressure rate were identified by preliminary inflation tests that were developed on further colon samples.…”
Section: Experimental Activitymentioning
confidence: 99%
“…4,15,16 Otherwise, tests can be developed at the structure level, as mechanical tests that are performed on tubular segments from a specific gastrointestinal region, as inflation tests. [17][18][19][20] The achieved data provide information about the overall structural response of the gastrointestinal region. In detail, results from such experimental activities make it possible to evaluate the actual elasticity and visco-elasticity of the gastrointestinal region, accounting for the real conformation of tissues, the fibres' contribution and the pre-stress conditions.…”
Section: Introductionmentioning
confidence: 99%